The Oslo Agreement in the Peace Process and the Role of the United States in Resolving the Palestinian-Israeli Conflict. - Silpiah; Siti Karomah; Siti Rosanti; Siti Mundiroh; Sri Ayuni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
This paper aims to find out the history or background of the Oslo agreement, the direction of policies and the efforts made in the peace of both parties and the results of the Oslo agreement. The results obtained by the author regarding the Oslo agreement are that the Oslo agreement occurred in 1993 against the background of land disputes in the West Bank and the Gaza Peninsula. Where the Israeli side asked Palestine to be officially recognized as the state of Israel. Meanwhile, Palestine asked to establish authority/self-government (occupied territory) in the Gaza Strip and the West Bank, but the relationship between the two sides continued to be damaged by the prolonged conflict, which resulted in losses for the surrounding population. So there was a negotiation for peace called the Oslo agreement. The Oslo Agreement is one of the important peace processes between Israel and Palestine that aims to resolve the prevailing conflict.